(untitled) (مجلة العلوم الشاملة, 2025)
Timely completion of construction projects remains a critical challenge in developing and post-conflict environments such as Libya, where persistent delays negatively affect project performance and economic development. This study investigates the factors affecting the real-time completion of construction projects in Al-Haraba city, Libya, based on stakeholder perceptions. A structured questionnaire survey was administered to construction professionals (n = 68), and the Relative Im-portance Index (RII) method was used to rank delay factors at both individual and group levels. The findings indicate that scheduling and control issues ranked highest (average RII = 0.7735), followed by financial constraints and change-related conditions, while stakeholder-specific differences were also observed. The results provide context-relevant evidence to support practical delay mitigation strategies and improve project delivery in the Libyan construction sector.